2006
DOI: 10.1159/000094019
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ω–3 Fatty Acids on Acute Necrotizing Pancreatitis in Rats

Abstract: The aim of this study was to investigate the influence ofω–3 fatty acids (ω3FA) on acute necrotizing pancreatitis (ANP) induced by glycodeoxycholic acid in rats. The induction of ANP resulted in significant increases in mortality rate, intestinal permeability, bacterial infection in pancreas and extrapancreatic organs, and serum activity of urea and amylase, alanine transferase (ALT), interleukin (IL)-6, tumor necrotizing factor-α (TNF-α), lactate dehydrogenase (LDH) in bronchoalveolar lavage (BAL) fluid, tiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 61 publications
2
9
0
Order By: Relevance
“…Rat studies of acute necrotizing pancreatitis have demonstrated that the infusion of omega-3 fatty acids reduces mortality, infections, and systemic inflammation. 46 Indeed, human studies of severe acute pancreatitis show decreased pulmonary and renal complications after omega-3 fatty acid treatment 47 and reduced infectious morbidity with glutamine-supplemented parenteral nutrition. 6 …”
Section: Discussionmentioning
confidence: 99%
“…Rat studies of acute necrotizing pancreatitis have demonstrated that the infusion of omega-3 fatty acids reduces mortality, infections, and systemic inflammation. 46 Indeed, human studies of severe acute pancreatitis show decreased pulmonary and renal complications after omega-3 fatty acid treatment 47 and reduced infectious morbidity with glutamine-supplemented parenteral nutrition. 6 …”
Section: Discussionmentioning
confidence: 99%
“…Recent studies indicate a beneficial effect of n-3 PUFA in the course of several diseases; however, the exact pathway is still unknown. 31 One pathway is supposed to be caused by a decrease of proinflammatory cytokines, prostaglandins, especially PGE 2 , and leukotrienes, especially leukotriene B4. 32,33 n-3 PUFA, especially those derived from fish oil such as eicosapentoeinic acid and DHA, are known to be integrated in the phospholipid pool of the cell membrane competing with arachidonic acid for the enzymes of the metabolization to eicosanoides.…”
Section: Discussionmentioning
confidence: 99%
“…Initially the right internal jugular vein was cannulated and catheter was tunneled subcutaneously to the suprascapular area for postoperative fluid resuscitation. ANP was induced by intravenous infusion of 5 mg/kg/h cerulein (Sigma-Aldrich, Munich, Germany) with superimposed infusion of 1.2 mL/kg glycodeoxycholic acid (Sigma and Aldrich, Germany) into biliopancreatic duct for 10 min at 30 mm Hg over 6 h following midline laparotomy [12]. Three mL of warm saline was applied to the abdomen before closing the midline laparotomy.…”
Section: Induction Of Pancreatitismentioning
confidence: 99%